Dyuta in the Sabhaparvan of the Mahabharata: Part of Rajasuya Sacrifice and/or Potlatch and/or Daiva and/or.. - Gonc-Moačanin, Klara (Array, 2005)
Klara Gonc-Moačanin questions the hypotesis of van Buitenen that the dramatic sabha events are a part of Yuddhistira's rajasuya. Then she discusses the interpretation of Gerrit Jan Held that the gambling episode describes a kind of potlatch, and refers to the ideas of David Schulman about the relaton between dicing, nikrti and daiva, and of Renate Sohnen Thieme that the driving force behind the game of dice is fate or destiny. After having shown, on the basis of the text itself and rich secondary literature, the incogruity of the narration with the ritual game of dice, an the possibility of using the term potlatch only in a metaphorical sense for the gaming episode, she presents various interesting covert connections between the dyuta and the concepts of dista and daiva